Digital financial and banking competition network: Evidence from China - Jia, Kaiwei; He, Ying; Mohsin, Mohammad (Frontiers in Psychology, 2023)
The rapid development of digital finance resulted in fierce competition in the banking industry. The study used Bank credit data to measure interbank competition based on social network model and digital finance development in different geographical locations. Additionally, we employed QAP (Quadratic Assignment Procedure) to empirically test the effects of digital finance on the competitive structure among banks, and explored its heterogeneity. The study finds that, large nation-owned banks have been a central position in the banking network system, with stronger competitiveness and higher strength of digital finance development. At the same time, the effect of digital finance accelerated the competition among banks, but also led to the increase of homogeneous competition. In addition, compared with large nation-owned banks, the competitiveness of small and medium-sized joint-equity commercial banks and urban commercial banks are more vulnerable to digital finance and resulting in homogenization problems. The above findings provide new ideas for the governance of banking competition and the realization of a new pattern of economic development.